Takotsubo Cardiomyopathy: One More Angiographic Evidence of Microvascular Dysfunction - Loffi, Marco; Santangelo, Andrea; Kozel, Martin; Kocka, Viktor; Budesinsky, Tomas; Lisa, Libor; Tousek, Petr (BioMed research international, 2018)
Background: Takotsubo cardiomyopathy (TC) aetiology has not been completely understood yet. One proposed pathogenic mechanism was coronary microvascular dysfunction (MVD). This study compared coronary flow and myocardial perfusion in patients with TC, microvascular angina (MVA), and a control group (CG). Methods: Out of 42 consecutive patients presented to our centre with TC from 2013 to 2017; we retrospectively selected 27 patients. We compared them with a sex- and age-matched group of 27 MVA cases and 27 patients with normal coronary arteries (CG). The flow was evaluated in the three coronary arteries as TIMI flow and TIMI frame count (TFC). Myocardial perfusion was studied with Blush-Score and Quantitative Blush Evaluator (QuBE). Results: TFC, in TC, revealed flow impairment in the three arteries compared to the CG (left anterior descending artery (LAD): 22 ± 8, 15 ± 4; p = 0.001) (right coronary artery: 12 ± 4, 10 ± 3; p = 0,025) (left circumflex: 14 ± 4, CG 11 ± 3; p = 0,006). QuBE showed myocardial perfusion impairment in the LAD territory in TC comparing with both the CG (8,9 (7,2-11,5) versus 11,4 (10-15,7); p = 0,008) and the MVA group (8,9 (7,2-11,5) versus 13,5 (10-16); p = 0,006). Conclusions: Our study confirmed that coronary flow is impaired in TC, reflecting a MVD. Myocardial perfusion defect was detected only in the LAD area.
Keywords: Coronary Angiography; lidé; Middle Aged; Coronary Vessels; takotsubo kardiomyopatie; Microvessels; Echocardiography; Female; rychlost toku krve; retrospektivní studie; infarkt myokardu; Humans; Myocardial Infarction; echokardiografie; lidé středního věku; koronární cévy; mužské pohlaví; Blood Flow Velocity; ženské pohlaví; koronární angiografie; mikrocévy; Male; Aged; Retrospective Studies; Takotsubo Cardiomyopathy; koronární cirkulace; Coronary Circulation; senioři